2017
DOI: 10.1371/journal.pone.0178426
|View full text |Cite
|
Sign up to set email alerts
|

The artificial sweetener acesulfame potassium affects the gut microbiome and body weight gain in CD-1 mice

Abstract: Artificial sweeteners have been widely used in the modern diet, and their observed effects on human health have been inconsistent, with both beneficial and adverse outcomes reported. Obesity and type 2 diabetes have dramatically increased in the U.S. and other countries over the last two decades. Numerous studies have indicated an important role of the gut microbiome in body weight control and glucose metabolism and regulation. Interestingly, the artificial sweetener saccharin could alter gut microbiota and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
4
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(182 citation statements)
references
References 60 publications
2
146
4
11
Order By: Relevance
“…To our knowledge, this is the first human study to report the impact of maternal consumption of ASB on the infant gut microbiome, and its potential influence on infant BMI. In light of recent data showing that ASB can drive dysregulation of energy metabolism in mice through changes in the gut microbiome 24,25,38,39 , our study suggests that infants exposed to ASB through their mothers may be at higher risk of shifts in microbial community structure related to early-life predisposition to metabolic diseases 40,41 .…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…To our knowledge, this is the first human study to report the impact of maternal consumption of ASB on the infant gut microbiome, and its potential influence on infant BMI. In light of recent data showing that ASB can drive dysregulation of energy metabolism in mice through changes in the gut microbiome 24,25,38,39 , our study suggests that infants exposed to ASB through their mothers may be at higher risk of shifts in microbial community structure related to early-life predisposition to metabolic diseases 40,41 .…”
Section: Discussionsupporting
confidence: 50%
“…As reported by Bian et al 38,39 in two studies with adult mice, and by Nettleton et al 43 in a study on dams and their offspring, ASB have been shown to alter gut bacterial community composition (increase of Bacteroides and reductions of Lactobacillus and Clostridium ) and increase body weight in parallel with an enrichment of energy metabolism bacterial genes. The functional cluster analyses by Bian et al 38,39 revealed activation of genes related to carbohydrate absorption and increases in metabolic pathways related to glycolysis and sugar and xylose transport 38 . Sucralose treatment resulted in an increase in bacterial pro-inflammatory mediator genes in mice 39 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Another recent study suggests that conventional cleaners and eco-friendly cleaners modulate the composition of the gut microbiota of infants leading to obesity at 3 years of age (Tun, Tun, & Mahoney et al, 2018). Likewise, exposure to artificial sweeteners (sucralose, acesulfame potassium, saccharin) has been associated with an altered gut microbiota and, ultimately, gut and intestinal inflammation, obesity, and diabetes (Bian et al, 2017a(Bian et al, , 2017bSuez, Korem, Zilberman-Schapira, Segal, & Elinav, 2015). Evidently there is a clear pattern in that the composition of the gut microbiota is shifted in different disease states; however, the exact mechanism by which this occurs remain unknown.…”
Section: Changes In Gut Microbiota In Different Disease Statesmentioning
confidence: 99%
“…These sweeteners have also not been tested for effects on the gut microbiota prior to approval. Effects from rodent studies include altered composition of microbes leading to impaired glucose tolerance [28,59,60], as well as increased pro-inflammatory potential [61,62] and liver inflammation [61]. NAS-induced alterations in microbiota composition leading to adverse metabolic outcomes should give rise to concern, especially because the demand for NAS containing products are increasing, and persons suffering from metabolic disorders could be more likely to choose such products for health benefits.…”
Section: Food Additivesmentioning
confidence: 99%